2009
DOI: 10.1002/stem.207
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Transplantation of G-CSF-Mobilized CD34+ Cells in Patients With Critical Limb Ischemia: A Phase I/IIa, Multicenter, Single-Blinded, Dose-Escalation Clinical Trial

Abstract: A number of preclinical studies have indicated the therapeutic potential of endothelial progenitor cells for vascular regeneration in ischemic diseases. A phase I/IIa clinical trial of transplantation of autologous CD34+ cells, the endothelial and hematopoietic progenitor‐enriched fraction, was performed in no‐option patients with atherosclerotic peripheral artery disease or Buerger's disease with critical limb ischemia (CLI). CD34+ cells were isolated from the G‐CSF‐mobilized apheresis product using a magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
160
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(171 citation statements)
references
References 24 publications
7
160
2
2
Order By: Relevance
“…As one of the stem cell therapies, PuCeT has demonstrated encouraging outcomes 2, 3. Similarly, in our pilot study conducted from 2009 to 2011, PuCeT demonstrated favorable early outcomes in AICLI 4.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…As one of the stem cell therapies, PuCeT has demonstrated encouraging outcomes 2, 3. Similarly, in our pilot study conducted from 2009 to 2011, PuCeT demonstrated favorable early outcomes in AICLI 4.…”
Section: Introductionsupporting
confidence: 63%
“…Many studies using different methods, such as vascular endothelial growth factor (VEGF)‐related gene transfer 6, 7, bone‐marrow mononuclear cell (BMMNC) 8, 9, 10, 11, 12, PBMNC 13, 14, 15, 16, 17, 18, or CD34+ cell 2, 3, 4 transplantation, have been completed and have proven their safety and efficacy. The long‐term outcome after CD34+ cell therapy in CLI patients was already reported by Kinoshita et al in 2012 19.…”
Section: Discussionmentioning
confidence: 99%
“…The classification cutoff value of 5 Â 10 7 is equivalent to about 1.0 Â 10 6 /kg, which was the highest dose of CD34 þ cells for which there was no significant dose-response relationship, as observed in a previous study (other doses were 1.0 Â 10 5 , 5.0 Â 10 5 and 1.0 Â 10 6 /kg). 20 Endpoints Endpoints were OS, defined as the time from the first day of treatment to death, and amputation free survival (AFS), defined as the time from the first day of treatment to the day of lower limb amputation or death. In this study, lower limb amputation refers to major (over ankle) amputation.…”
Section: Measurementmentioning
confidence: 99%
“…In the past decade, many cell therapies for CLI have been developed. The types of therapeutic cells used till date have been bone marrow mononuclear cells (BMMNC), 2-11 PBMNC, 2,12,13 G-CSF-mobilized (M)-PBMNC, [14][15][16][17][18] CD34-antigen-positive mononuclear cells 19,20 and CD133-antigen positive cells. 21 Although BMMNC or M-PBMNC intramuscular implantation has been used most often, both therapies have some risk: to collect about 500 mL of BMMNC, general anesthesia of about 4 h duration is necessary, and to collect PBMNC, about 3 h of apheresis with G-CSF treatment is required.…”
Section: Introductionmentioning
confidence: 99%
“…To date, surgical therapies such as bypass grafting or endarterectomy (or conventional revascularization therapies such as angioplasty, intravascular stents, or intra-arterial thrombolysis) are considered the most promising treatment options for ischemic limbs; however, these methods can be used to treat only approximately 5% of patients with PAD or CLI. Furthermore, persistent effects are observed in approximately 25% of patients after revascularization (Kawamoto et al 2009). Hence, the development of a novel therapeutic strategy to improve the prognosis of patients with PAD and those with CLI is required.…”
Section: Introductionmentioning
confidence: 99%